Controle biológico de thaumastocoris peregrinus (Hemiptera: thaumastocoridae) com fungos entomopatogênicos - Soliman, Everton Pires [UNESP] (2014)
Thaumastocoris peregrinus spread rapidly over Brazilian eucalyptus plantatio ns after 2008; since then, studies on biological control wit h predators, egg parasitoids and entomopathogenic fungi have been conducted to enabl e its integrated management. This work proposal aimed at: estimating the control effi ciency of mycoinsecticides to the bronze bug; evaluating the compatibility between insectici des and entomopathogenic fungi; studying and identifying fungi associated with the occurrence of epizootics in the field; and evidencing the control efficiency in the field of t he fungi and the pesticides. Under laboratory conditions, in the dose of 1 x 10 8 conidia/ml Beauveria bassiana (products BUS and BIT), Metarhizium anisopliae (MIT, MTO e MUS), Fusarium proliferatum (FUS) and Lecanicilum longisporium (VIT) were pathogenic to the pest, in this same cr escent order of efficiency. Both products with B. bassiana showed mortality rate superior to 90%, being the adults more susceptible than the nymphs to B. bassiana , M. anisopliae and F. proliferatum . The total production of conidia in the corpses (n ymphs more than adults) of T. peregrinus was superior for BUS, BIT, MTO and VIT. The increa se in dosage of the insecticide or adjuvant from 1 to 10000 ppm reduced fungi growth in petri dishes; the dose of 10000 ppm (10g/L) of imidacloprid, mineral oil, vegetal oil, bifenthrin and thiamethoxam affected negatively the growth of FUS, BUS and BIT; MIT was affected only by the last three pesticides. In the indexatio n of compatibility, there was intraspecific variation in the B. bassiana isolates. The field epizootic demonstrated suscept ibility of the pest to the fungi, with high rate of population con trol. From the field, Aspergillus sp. e Cladosporium sp were isolated and caused adult mortality in labo ratory assay. In the field, the susceptibility of the pest to the insecticides thiamethoxam, lambda-cyhal ...